Herbal face pack formulation from Citrullus lanatus - Mhamane, Supriya (Indian Journal of Pharmacy & Drug Studies, 2024)
Watermelon (Citrullus lanatus) belongs to the family Cucurbitaceae. Even though watermelon is commonly classified as a vegetable, it is botanically considered as a fruit and used primarily as a dessert. The main aim of this study is, to evaluate and formulate the Citrullus lanatus face pack. Watermelon rind powder, turmeric powder and sandal wood powder were used for this formulation. The dried powders were mixed and passed from sieve no. 120. Particle size of the powder was found to be 125 micron. The organoleptic evaluations, irritancy test, rheological evaluations, pH value, ash value determination, moisture content evaluation were performed. The herbal face pack is used to stimulate blood circulation, recreate the muscle, regulate the elasticity of skin and cleansing the skin. The herbal formulations has the less side effects. So, we decided to work on the herbal face pack.